Anesthetic Management of the Patient With Dilated Cardiomyopathy Undergoing Pulmonary Resection Surgery: A Case-Based Discussion. (March 2013) - Sumler, Michele L.; Andritsos, Michael J.; Blank, Randal S.
Interactions between the cardiovascular and respiratory systems are complex and profound. General anesthesia, muscle relaxation, and positive-pressure ventilation all impose physiological effects on cardiovascular function. In patients presenting for pulmonary resection, additional effects resulting from positioning, 1-lung ventilation, surgical procedures, and contraction of the pulmonary vascular bed may impose an additional physiological burden. For most patients with adequate pulmonary and cardiovascular reserve, these effects are well tolerated. However, the cardiothoracic anesthesiologist may be asked to provide anesthetic care for patients with significantly reduced cardiac function who require potentially curative pulmonary resection for lung cancer. These patients present a major perioperative challenge and a thoughtful approach to intraoperative management is required. The authors review a case of a patient with severely impaired biventricular function who presented for elective pulmonary lobectomy in an attempt to effect a curative resection of lung cancer and present a discussion of physiological and pathophysiological considerations for clinical management.